PENGARUH PROMOSI SEKOLAH TERHADAP KEPUTUSAN SISWA DALAM PEMILIHAN SMK SEPULUH NOPEMBER SIDOARJO - Raditya Gusdiandika; Kukuh Sinduwiatmo (Kanal: Jurnal Ilmu Komunikasi, 2012)
This study aims to determine the effect of the promotion toward the student's decision in choosing Sepuluh November vocational school of Sidoarjo. The variables in this study are the promotion of schools as independent variable and the decision to choose as the dependent variable. The subjects were 94 students of Sepuluh November vocational high school selected using proportionate stratified random sampling technique. Promotions and informed choice are measured using school promotion scale and the choosing decisions scale compiled by the researcher. From the results of the data analysis using regression analysis techniques aided by SPSS 16.0 for Windows, it was obtained that (thitung = 3.060; ρ = 0.003; ρ <0.05), the alternative hypothesis accepted that there was an effect of school promotion on the decision of the students tochoose Sepuluh November vocational high school. Based on the value of R square = 0.092 / 9.2% of students decisions is affected by the school promotional activities, while the remaining percentage influenced by other factors. Based on the value of multiple correlation (R) it is obtained at 0.304, it can be seen from the table below where it shows that relations campaign against the decision of the school students in choosing Sepuluh November vocational high school of Sidoarjo classified in the range of 0.20 to 0.39 points, which means that the level of relationship is low but definite.